The phenotype characteristics and decline population of Sawang duck in Sawang Village, Karimun Regency, Riau Islands Province - Hidayati Hidayati; Desrita Desrita (Faculty of Animal Science, Universitas Brawijaya, 2021)
Sawang duck is one of Indonesia's local dual-purpose type ducks due to the offspring of Tsaiya ducks originating from Taiwan. Tsaiya ducks enter the Sawangarea, brought by residents from Singapore around 1955 and subsequently bred in the Sawang Village, adapting to the environment and the local farming. This research was conducted in August-December 2018. Primary data on the qualitative, morphometric, and potential feed were taken in Sawang Village, Karimun Regency, Riau Islands Province. Currently, Sawang duck is only found in Sawang Village, maintained by two farmers. Secondary data of potential areas and poultry populations were obtained from the Department of Food and Agriculture of Karimun Regency, and proximate analysis was carried out at the Ruminant Nutrition Laboratory, Faculty of Animal Husbandry, Andalas University. The research method was conducted by survey with census sampling techniques. The Sawang duck has a diversity of colors for feather, skin, beak, and shank. The morphometric decrease was indicated by bodyweight of 1,450 ± 119.52 grams, femur length of 7.41 ± 1.62 cm, tibia length of 9.94 ± 0.51 cm, length of shank 4.38 ± 0.25 cm, third finger length 6.36 ± 0.90 cm, maxilla length 5.21 ± 0.16 cm, backbone length 20.13 ± 1.13 cm, wing bone length 26.65 ± 1.70 cm, bone length chest 10.63 ± 0.80 cm, and shank circumference 1.24 ± 0.10 cm. Efforts to preserve ducks Sawangneed to be considered so that their existence is not destroyed by exploiting the existing area's potential.